Students’ Needs towards Learning Arabic Language Via the Electronic Network: Saraf Unit as a Model: Language Learning - Ahmad Rashidi, Aishin Nada; Seman, Haji Mohammad; Hussin, Mohamad (Al-Ḍād Journal, 2024)
This study aims to reveal the needs of non-Arabic students in learning the Arabic language via e-learning using morphology units as a model. This study was conducted at the University of Kuala Lumpur Business School (UniBis), where the Arabic language is a compulsory subject that students from Islamic Finance and Tourism Planning and Development programs are required to complete. The students’ needs were measured by a close-ended questionnaire. The data were analyzed using the Statistical Program for Social Sciences (SPSS) to find out the percentage, frequency and mean. The findings show some important results in solving students’ problems and their needs to use multimedia elements in online learning. The students are in need of learning the Arabic language via online platforms as they do not encounter many problems in using it and the use of multimedia is important to improve their understanding. Keywords: Students’ needs and problems; Morphology unit; Online learning; Multimedia elements.